Sequential energy and electron transfer in polynuclear complex sensitized TiO2 nanoparticles - Verma, Sandeep; Kar, Prasenjit; Banerjee, Tanmay; Das, Amitava; Ghosh, Hirendra N. (Journal of Physical Chemistry Letters, 2012)
Polynuclear–polypyridyl complexes exhibit a directional energy-transfer property that can improve their photosensitization activity. In the present work, the energy-transfer process is explored in a trinuclear Ru2∧Os1 complex using transient absorption spectroscopy. This study reveals an efficient excitation energy transfer from the terminal (RuII complex) to the core (OsII complex) region in the ultrafast time domain (400 fs–40 ps). The excitation energy funnel is useful in improving the functionalized core activity. This is evidenced in an interfacial electron-transfer study of Ru2∧Os1, Ru2∧Ru1, and Os1 complex sensitized TiO2 nanoparticle (TiO2 NP) systems. The intramolecular energy transfer causes sequential excitation of the core part of the Ru2∧Os1 complex, which leads to multiexponential electron injection into TiO2 NP. Besides this, the electronic coupling between the metal ion centers stabilizes the positive charge within the trinuclear complex, which results in a slow charge recombination reaction. This study shows that polynuclear complexes can be very useful for their panchromatic effects, unidirectional energy- and electron-transfer properties.

Size quantization effects on interfacial electron transfer dynamics in Ru(II)-polypyridyl complex sensitized ZnO QDs - Verma, Sandeep; Das, Amitava; Ghosh, Hirendra N. (Journal of Physical Chemistry C, 2014)
Quantum-size confinement in semiconductor material offers size based tunability of interband gap energy as well as intraband sublevels. In this work, size quantization of wide bandgap ZnO quantum dots has been explored in the study of interfacial charge separation reaction using a catechol functionalized Ru(II)polypyridyl complex as a photosensitizer molecule. Femtosecond time-resolved transient absorption studies have revealed multiple electron injection events based on discrete conduction band states of ZnO QDs. The electron injection rates have been rationalized for quantum confinement effects owing to different sizes of ZnO QDs. Furthermore, the size dependency of the intrinsic lifetime of electrons injected into discrete energy levels of ZnO QDs has been revealed in charge recombination reaction with the Ru(III)polypyridyl complex cation. The charge recombination dynamics reveals a competing trend of carrier confinement and carrier leak upon reducing particle size. This study shows the optimization of finite size effects in achieving better interfacial charge separation at the dye/semiconductor interface.